Preferred Leadership Traits by Employees : A case study in Telecommunication Organization - Charles, Maizan; Florianna Lendai, Anak Michael Mulok; Hana, Binti Hamidi (UNIMAS Publisher, 2019)
Leaders affect employees’ performance in the organization by their leadership style, which is dependent to the degree of favor by their followers. It is vital for the organization to identify the most effective leadership styles which will boost performance in the organization. This research studied the type of leadership trait most preferred in the telecommunication sector. This qualitative study used the Full Range Leadership Model to identify and suggest the preferred traits of a leader. The sampling method used was purposive. Interview guides were used as the research tool. A total of six (6) informants were interviewed. The results showed transformational leadership style is the most preferred by all the informants as the employees found that the traits of the transformational leader bring more positive impacts on their work performance.